Differentiation of thermal properties of pollens on genus level - Mujtaba, Muhammad; Kaya, Murat; Ceter, Talip (Ankara University, 2018)
This study was carried out to explain the thermal properties of pollen grains for three different genera. It was also aimed to determine how thermal properties are differed in pollen grains belong to different genera. The pollen genera Salix, Betula and Fraxinus were chosen. The observed results showed that pollen grains of different genus exhibits an important difference in their thermal stabilities. The thermograms of species belonging to Fraxinus genus revealed a five-staged thermal degradations while species from Salix and Betula genus revealed a fourstaged thermal degradations. As is know very well, pollen grains are diamond of plant word and they have many applications in cosmetic, pharmacy, food and medical industry. The findings of the current study will be helpful for the future applications of pollen as a material in different fields
Keywords: Thermal stability; pollen; genus level; Salix; Betula; Fraxinus